2018
DOI: 10.1016/j.eurpsy.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of transcranial alternating current stimulation for treatment of auditory hallucinations in schizophrenia

Abstract: To our knowledge, this is the first clinical trial of tACS for the treatment of symptoms of a psychiatric condition. Further studies with larger sample sizes are needed to better understand the effect of tACS on auditory hallucinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 33 publications
4
92
1
1
Order By: Relevance
“…Therefore, tACS might offer similar potential for other disorders. We reference the reader to recent studies investigating tACS effects in such disorders (Ahn et al 2019;Alexander et al 2019;Mellin et al 2018). Furthermore, this study presented first support that tACS could be used to increase the amplitude of the P300 using its respective EROs as targets.…”
Section: Closing Commentsmentioning
confidence: 53%
“…Therefore, tACS might offer similar potential for other disorders. We reference the reader to recent studies investigating tACS effects in such disorders (Ahn et al 2019;Alexander et al 2019;Mellin et al 2018). Furthermore, this study presented first support that tACS could be used to increase the amplitude of the P300 using its respective EROs as targets.…”
Section: Closing Commentsmentioning
confidence: 53%
“…Increasing the reliability of low-intensity tES is one of the major challenges for the brain stimulation community. An understanding of the factors determining successful modulation of outcome measures by tES is crucial as the field is advancing these techniques towards clinical applications [5][6][7] . In the current study, we demonstrated that the variability of tACS aftereffects can be explained by an interplay of factors qualitatively capturing the targeting of the stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Among these techniques, transcranial electrical stimulation (tES) using weak direct (tDCS) or alternating (tACS) currents are of particular interest as they provide safe and tolerable stimulation at low costs and high portability 3,4 . These features render tES approaches promising for a wide range of clinical applications [5][6][7] . While tDCS is thought to exhibit its effect by changing neuronal excitability via alterations of neuron's resting membrane polarization 1, [8][9][10] , tACS is believed to work via the principles of neuronal entrainment 2,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, our crossover study design only allowed for one session of active stimulation. TACS may have an additive effect on modulating oscillations if a design with multiple sessions were used (75,76).…”
Section: Discussionmentioning
confidence: 99%